PERANCANGAN PROGRAM APLIKASI PEMESANAN PADA PT. TOP EDISIA NIAGA (MIDTOWN OWL CAFE) - Christyanto, Leonardo (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
PT. Top Edisia Commerce (Midtown Owl) is a café which was established on December 23, 2012. Computerized system which runs on this café is not maximized because computerization is only used to store financial data, resulting in accumulation of the file. The purpose of the program is to maximize the application all data processing in the cafe. The methodology to design the application program is SLDC (System Development Life Cycle). These applications use PHP as the programming language, MySQL as database, server Wamp and Notepad ++ to design this program. Key words SDLC, PHP, MySQL